Morphological, physical and chemical attributes of the soil profile to the right margin of the Paraguay river, Baia da Campina, Cáceres (MT) - Martins-Oliveira, A. T.; Stefanello, L. E. S.; Santos, T. M.; Pinto, V. R.; Souza, C. A.; Sousa, J. B. (Scientific Electronic Archives, 2020)
The fluvial dynamics corresponds to the natural changes of river channels that can influence the water energy, type and morphology of the gutter, geological structure and soil types. In this context, the type of soil present on the banks of the rivers stands out, which due to their morphological, physical and chemical characteristics, will offer greater or less resistance to marginal erosive processes. Whit this study, we aim to verify the contribution of soil morphological, physical and chemical attributes in the natural dynamics of the right bank of the Paraguay River. The studied area is located in the Pantanal Matogrossense, sub-region of Cáceres, and comprises the right bank of the Paraguay River, in the region of Baia da Campina, approximately 10 km away from the municipality of Cáceres, Mato Grosso, Brazil. We carry out morphological, granulometric and chemical description of the soil. The data were tabulated in a spreadsheet, being subsequently analyzed and discussed. The vegetation occurring in the study area is of the seasonal / cerrado and alluvial forests type, with the presence of low and semi-shrub vegetation. We classified the soil profile in the section studied as Fluvic Tb Endoeutrophic Neosol, presenting medium texture and, in general, high levels of sand and low levels of clay. The values referring to the effective cation exchange capacity (CTC) obtained in this study, were classified from low to very good, a characteristic that allows the existence of low and semi-shrubby vegetation, which contributes to the resistance to erosive processes, even that the soil has a low presenting resistance physical structure.